Teknik Penokohan dalam Novel Negeri Lima Menara Karya Ahmad Fuadi - Yustina Yaku Tia; Simon Sabon Ola; Margaret P.E. Djokaho (YASIN, 2026)
Although Ahmad Fuadi’s novel Negeri Lima Menara has been widely studied, research specifically analyzing characterization based on the elements of B. F. Skinner’s behaviorism remains limited. This study aimed to describe characterization in the novel based on the elements of stimulus, response, behavior, reinforcement, and environment. This study employed a qualitative descriptive method with a behavioral psychology approach. The data source was the novel Negeri Lima Menara, while the data consisted of excerpts depicting the characters’ traits. The data were collected by reading, closely examining, recording, and grouping the excerpts according to the elements of behaviorism and were then analyzed through the stages of identification, classification, and description based on the theory employed. The findings showed that Alif’s characterization was constructed through the interrelationships among stimulus, response, behavior, reinforcement, and environment. Family encouragement, the motto Man Jadda Wajada, and the Pondok Madani environment served as stimuli associated with shaping Alif into a disciplined, persistent, rule-abiding, socially caring, and religious individual. Positive and negative reinforcement strengthened the formation of these traits, while the family and Pondok Madani constituted the dominant environments in his personality development. This study concludes that the behavioral approach can systematically explain the process of character formation. These findings contribute to the development of literary psychology studies and can serve as a reference for literature learning and character education.